The role of neologisms in the modern literary language - Saminjonova Shakhnozahon Numanovna , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the issue of neologisms, their place and functioning in the modern Russian literary language, the classification of neologisms is given, an attempt is made to clarify the appearance of neologisms in the language and their distribution.